2017
DOI: 10.1136/jech-2016-208671
|View full text |Cite
|
Sign up to set email alerts
|

Education and health and well-being: direct and indirect effects with multiple mediators and interactions with multiple imputed data in Stata

Abstract: This study contributes to the literature on mediation analysis, as well as the literature on the importance of education for health-related quality of life and subjective well-being. The influence of education on health and well-being had different pathways in this Norwegian sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(74 citation statements)
references
References 82 publications
5
68
1
Order By: Relevance
“…The variable childhood financial conditions was used as a proxy for childhood socioeconomic status, and was measured retrospectively by the question: "How was your family's financial situation when you were a child?" on a 4-point scale (1=very good, 2=good, 3=difficult, 4=very difficult) [64,1,2,9,3,54,4]. The test-retest reliability of childhood financial conditions was good (Kappa weighted : 0.61, 95% CI: 0.59-0.63) in this sample [3,4].…”
Section: Confounding Variables (Tromsø Iv)mentioning
confidence: 75%
See 2 more Smart Citations
“…The variable childhood financial conditions was used as a proxy for childhood socioeconomic status, and was measured retrospectively by the question: "How was your family's financial situation when you were a child?" on a 4-point scale (1=very good, 2=good, 3=difficult, 4=very difficult) [64,1,2,9,3,54,4]. The test-retest reliability of childhood financial conditions was good (Kappa weighted : 0.61, 95% CI: 0.59-0.63) in this sample [3,4].…”
Section: Confounding Variables (Tromsø Iv)mentioning
confidence: 75%
“…First, assessing mediation with cross-sectional studies can lead to questionable inferences [2,54], as studies have shown reciprocal associations between perceived social isolation and internalizing symptoms [55,38,56]. Studies with dense temporal sampling are also vulnerable to these biases [54]. A potential solution for establishing temporal order between perceived social isolation and internalizing symptoms is a long follow-up period [54,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed illustrations can be found in the excellent texts of Aguinis (2004), Aiken and West (1991), Hayes (2013), and Jaccard and Turrisi (2003). Moreover, a related study of direct and indirect effects with multiple interactions is presented in Sheikh, Abelsen, and Olsen (2017). The statistical procedure for detecting the interactions between continuous and categorical variables is methodologically identical to that for testing the equality of slope coefficients in two or more regression lines.…”
Section: Introductionmentioning
confidence: 99%
“…Educational success is important for future health and economic well-being. 7 Therefore, it is important to investigate whether children with AD are at risk of lower educational attainment and if so to determine the underlying mechanisms. This knowledge will assist in planning interventions to support children during their lives.…”
mentioning
confidence: 99%